The influence of transformational policies on the operational competitiveness of South African businesses - L. P. Krüger (South African Journal of Business Management, 2013)
Since the dawn of democracy in South Africa in 1994, transformational policies such as black economic empowerment (BEE) and affirmative action (AA) have increasingly and inextricably become part of the everyday political, economic and social life of its populace. As a result, South African businesses are subject to a whole array of mandatory regulations which ostensibly influence their operational capabilities to effectively and efficiently compete in national and global markets. In a survey of the largest 500 (including the top 100 JSE listed) companies in South Africa, it appears that transformational policies are positively supported and endorsed, although their impact on the operational competitiveness of these companies is largely unclear and unknown. A number of warning signs, however, are now being detected from reports in the popular media and in the academic literature about the possible negative consequences of such policies. BEE malpractices, which basically result in the continuation of past injustices against the majority of poor and unskilled people of the country, are becoming increasingly evident. Even more alarming is the fact that the corruption, nepotism and self-enrichment that accompany most BEE transactions are attributed to the ruling ANC political elite.